Ensaios sobre a migração de retorno interestadual no Brasil. - Ferreira, Allyne de Almeida (2012)
The main objective of this study is to analyze the effect of experience of interstate migration in Brazil on the productive reinsertion and on the income of the employee that returned to the region of origin. The data used in this study were derived from the National Household Sample Survey (PNAD) of 1999 and 2009. This study is divided into three sections. The first is reserved for the investigation of the migratory pattern inside the Brazilian territory and for the comparison of the socioeconomic attributes of return migrants with those observed for non-migrants and non-returned migrants. In the 2000s, the evidences show that most migrants of return comes back to the Northeast and, also, that Southeast has sent more people who received, indicating a loss of attractiveness. The again migrated worker can be characterized as an individual male, nonwhite race, urban person and head of family, being, on average, younger, more educated and better paid than non-migrant. On the other hand, the migrated worker again is older, less educated and receives lower income than non-returned migrant. In the second part are analyzed the determination of the condition of migration and salary differentials between categories: interstate migrants of return, interstate non-returned migrant and non-migrant. The methodology consisted in estimating a structural model of joint determination of migration, remigration and wages, with the application of the method of Lee (1978) for the correction of possible sample selection bias. Moreover, wage differentials were calculated using the technique of Oaxaca-Blinder-Oaxaca and Ramson. The empirical findings show that male workers, more educated, employed as self-employed and entrepreneurs were more inclined to interstate migration and remigration to the state of birth. And, in relation to profits, show that male workers, more educated, employed as civil servants and entrepreneurs, profited higher values. But, the non-returned migrants and the migrants of return received higher incomes than non-migrants. These differences are mainly explained by unobserved characteristics, indicating a positive selection of migrants on attributes not observed in relation to non-migrants. Finally, the objective of the third part was to investigate the impact of the accumulation of savings and/or wealth in the decision to occupation of interstate migrants of return. The methodology used in that investigation was to estimate a probit model with endogenous regressor, correcting the bias this endogeneity in wealth accumulation. Empirical evidences enabled to identify that accumulation of wealth had a positive impact on the choice to employ themselves as self-employed and entrepreneur. Furthermore, the return migrants more favorable to self-employment or entrepreneur are men, white, aged older, with low schooling and that living in the North, Northeast and Midwest regions. In relation to the accumulation of wealth, were also verified that workers who returned before 2000 have accumulated more wealth than workers of recent decade and the accumulation of wealth was generated during the period of youth of the workers.